2019
DOI: 10.1108/qaoa-03-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Marketing of surveillance technology in three ageing countries

Abstract: Purpose The purpose of this paper is to review marketing materials of surveillance products for people with dementia and their carers in three ageing countries, as part of a dementia-technology media analysis. Design/methodology/approach An online environmental scan was conducted using search terms for surveillance technologies (STs) and dementia through a Google search focussed on the UK, Sweden and the Netherlands. Data were extracted on the products’ and websites’ marketing messages from consumer and mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Feedback on the presented advertisement yers indicated that product marketing has a large room for improvement in terms of content and visuals. Similar to recent studies (42,43), professionals' stressed the importance of placing end-users at the center of marketing activities to reduce stigmatizing keywords and visuals, as well as to ensure that information on functionality and data security are transparently and adequately addressed.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Feedback on the presented advertisement yers indicated that product marketing has a large room for improvement in terms of content and visuals. Similar to recent studies (42,43), professionals' stressed the importance of placing end-users at the center of marketing activities to reduce stigmatizing keywords and visuals, as well as to ensure that information on functionality and data security are transparently and adequately addressed.…”
Section: Discussionmentioning
confidence: 78%
“…Third, the nding that recommendations regarding product pricing were not explicitly discussed in the third section although purchase cost was mentioned as a pivotal barrier for product adoption can be seen as a limitation. This limitation is not unique to our work, and past research with end-users also generally reports a high range of acceptable purchase costs which typically range from 20 to 100 dollars (42).…”
Section: Discussionmentioning
confidence: 97%
“…However, PPI is often criticised as an exclusive and tokenistic practice involving a narrow group of experienced members [67]. INVOLVE, [2012] created briefing notes for researchers involving the public and NIHR, [68] recommended to continuously improve the development of PPI by beginning with diversity and inclusion [66; 68]. Despite these criticisms, PPI can improve the quality and relevance of research and lead to the empowerment of those members involved.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…Surveillance, on the other hand has a more specific purpose. A previous study found that simple lowtech trackers were sold to track not only people with dementia, but also dogs and prisoners [68]. Companies are looking for a market and surveillance is what the market offers for dementia [61].…”
Section: Leave the "Technology" Out Of "Surveillance Technology"mentioning
confidence: 99%
“…17 Technological products to support those who wander have been available since the 1980s; 18 however, many ST products available for purchase online continue to be nonpreventative devices, which track but do not send alerts. 19 For example, even in April 2018 only half of the ''top 10 lifesaving location devices for dementia'' include GPS. 20 Previous research has mainly focused on needs related to the broader category of AT, 21 through focus groups, interviews, questionnaires, and ethnographic studies.…”
Section: Introductionmentioning
confidence: 99%